2018
DOI: 10.1007/s11239-018-1718-y
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of Batroxobin in combination with anticoagulation on cerebral venous sinus thrombosis

Abstract: Cerebral venous sinus thrombosis (CVST) is an uncommon subtype of stroke with highly variable clinical presentation. Although anticoagulation with heparin and/or warfarin remains the standard treatment for CVST, treatment failure is still common. This study aims to evaluate the safety and efficacy of Batroxobin in combination with anticoagulation on CVST control. In this retrospective study, a total of 61 CVST patients were enrolled and divided into Batroxobin (n = 23) and control (n = 38) groups. In addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 27 publications
2
33
2
Order By: Relevance
“…NIHSS scores and mRS scores at discharge and 6 months were equivalent between the patients with batroxobin use and controls in the previous study. Only discharge NIHSS scores were significantly better in batroxobin group . The current study revealed no significant differences in NIHSS or mRS at follow‐up.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…NIHSS scores and mRS scores at discharge and 6 months were equivalent between the patients with batroxobin use and controls in the previous study. Only discharge NIHSS scores were significantly better in batroxobin group . The current study revealed no significant differences in NIHSS or mRS at follow‐up.…”
Section: Discussioncontrasting
confidence: 57%
“…The MRBTI map gave us direct visualization of clot elimination with nonionizing radiation suggesting this may be a new noninvasive accurate way of following CVT patients. The elevation of D‐dimer (more than 20‐fold of baseline) and reduction in fibrinogen after batroxobin use presented in the previous study provide a convincing demonstration that fibrinolysis and thrombolysis induced by batroxobin can dissolve CVT thrombus …”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations